2023
DOI: 10.1097/xcs.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making in General Surgery: Prospective Comparison of Telemedicine vs In-Person Visits

Abstract: BACKGROUND: The coronavirus disease 2019 (COVID-19) pandemic has accelerated a shift toward virtual telemedicine appointments with surgeons. While this form of healthcare delivery has potential benefits for both patients and surgeons, the quality of these interactions remains largely unstudied. We hypothesize that telemedicine visits are associated with lower quality of shared decision-making. STUDY DESIGN: We performed a mixed-methods, prospective, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Delivering patient-centered care, which includes patient participation and shared decision-making, is a highly valued competency for all healthcare professionals [ 10 , 11 ]. While shared decision-making in ‘virtual’ appointments has been shown to be comparable to in-person visits in other areas of healthcare [ 1 , 26 ], literature on shared decision-making in an emergency care team context involving telemedicine is missing. In this study, we observed low levels of ‘sharing power’, including shared decision-making, in both settings.…”
Section: Discussionmentioning
confidence: 99%
“…Delivering patient-centered care, which includes patient participation and shared decision-making, is a highly valued competency for all healthcare professionals [ 10 , 11 ]. While shared decision-making in ‘virtual’ appointments has been shown to be comparable to in-person visits in other areas of healthcare [ 1 , 26 ], literature on shared decision-making in an emergency care team context involving telemedicine is missing. In this study, we observed low levels of ‘sharing power’, including shared decision-making, in both settings.…”
Section: Discussionmentioning
confidence: 99%
“…After the visit, patients do not receive any communication reminding them to schedule the test or referral, which may further limit loop closure. Other potential explanations include the possibility that it may be more difficult to remember information provided during telehealth visits, that telehealth may present unique communication barriers, or that it may be more difficult to engage patients in shared decision-making during virtual visits, thus decreasing patient engagement with test and referral orders …”
Section: Discussionmentioning
confidence: 99%
“…Other potential explanations include the possibility that it may be more difficult to remember information provided during telehealth visits, that telehealth may present unique communication barriers, or that it may be more difficult to engage patients in shared decision-making during virtual visits, thus decreasing patient engagement with test and referral orders. [18][19][20][21] These barriers may be more pronounced for colonoscopies compared with other types of orders given the increased difficulty in preparing for and completing the invasive procedure, thus explaining the disparities in loop closure compared with the other orders included in our analysis. 22 Furthermore, given the notable difference in loop closure for colonoscopies, telehealth visits may serve as a marker for patients not participating in a high-complexity test.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…Virtual care (VC) takes place whenever technology facilitates care delivery 9 . VC sometimes can promote SDM; for example, surgery patients reported equivalent quality of SDM during VC versus in‐person visits 10 . Unfortunately, other accounts demonstrate challenges.…”
Section: Introductionmentioning
confidence: 99%
“… 9 VC sometimes can promote SDM; for example, surgery patients reported equivalent quality of SDM during VC versus in‐person visits. 10 Unfortunately, other accounts demonstrate challenges. Patients with RCCs stated that they “lost their voice” when VC emerged, and analyses of teleconsultations among primary care providers, specialists, and patients showed reduced patient participation.…”
Section: Introductionmentioning
confidence: 99%